Exploring the Validity of the Perceived Restorativeness Soundscape Scale: A Psycholinguistic Approach - Payne, Sarah R.; Guastavino, Catherine (Frontiers in Psychology, 2018)
Soundscapes affect people’s health and wellbeing and contribute to the perception of environments as restorative. This paper continues the validation process of a previously developed Perceived Restorativeness Soundscape Scale (PRSS). The study takes a novel methodological approach to explore the PRSS face and construct validity by examining the qualitative reasons for participants’ numerical responses to the PRSS items. The structure and framing of items are first examined, to produce 44 items which are assessed on a seven-point Likert agreement scale, followed by a free format justification. Ten English speaking participants completed the PRSS interpretation questionnaire in two cafes in Montréal, Canada. Interpretation of participant free format responses led to six themes, which related to either the individual (personal attributes, personal outcomes), the environment (physical environment attributes, soundscape design) or an interaction of the two (behaviour setting, normality and typicality). The themes are discussed in relation to each Attention Restoration Theory (ART) component, namely Fascination, Being-Away, Compatibility, and Extent. The paper concludes by discussing the face and construct validity of the PRSS, as well as the wider methodological and theoretical implications for soundscape and attention restoration research, including the terminology importance in items measuring ART components and the value of all four components in assessing perceived restorativeness.